Comparing Neonatal Intensive Care Unit Nursing Support in Mothers With ‎Newborn Abstinence Syndrome (NAS) and Mothers of Healthy Neonates - Hosseini, Seyedeh Najmeh; Ghodousi, Arash; Sadeghi, Narges; Abbasi, Somayeh (International journal of medical toxicology and forensic medicine, 2019)
Background: The experience of having neonates in the Neonatal Intensive Care Unit (NICU) is a psychological crisis. It might cause many emotional problems for parents. Entire parental support is among the duties of the healthcare team. Therefore, this study aimed to compare the nursing support received by the mothers with Newborn Abstinence Syndrome (NAS) and the mothers of other neonates admitted to the NICU. Methods: The present cross-sectional descriptive-analytic study was conducted in the selected hospitals in Kerman Province, Iran. In total, 62 mothers with NAS and 61 non-addicted mothers with neonates admitted to the NICU were selected through convenience sampling method. The inclusion criteria were neonates under the care of parents, neonate admitted to the NICU for at least 24 hours, opiate dependence in the case group mothers, and no substance dependence in the control group mothers. The amount of nursing support for mothers having neonates with NAS was compared with that of the control mothers. The study groups were homogenized in terms of the study variables (neonate age, gender, and the duration of hospitalization). The required data were collected by the Nurse-Parent Support Tool (NPST) and analyzed in SPSS. Results: The study results revealed that among the neonates of 123 mothers, 75(60.97%) were boys, and 58(39.02%) were girls. The majority of neonates in both groups were breastfed. The mean±SD age of the mothers in the case and control group were 31.93±7.25 and 28.99±4.36 years, respectively. The nursing support level was desirable in both groups, and no significant difference was found in this regard (P>0.05). Furthermore, the level of nursing support in emotional, information-communication, self-esteem, and quality caregiving support dimensions was desirable in both groups. Conclusion: The obtained results revealed that nurses’ support was desirable in both groups. The prevalence of maternal addiction and the impact of this social harm on neonates who were admitted are essential. Furthermore, families having neonates with NAS need more support from the healthcare staff and nurses, in comparison with healthy parents; thus, the importance of this issue should be addressed in training and briefing courses for nurses.